(untitled) (Nepalese Journal of Radiology, 2020)
Introduction: Compensatory hypertrophy of inferior turbinate in the contralateral side of the deviated nasal septum is a known phenomenon. The objective of this study was to establish the relationship between the nasal septum and inferior turbinate and to determine the dimension and composition of inferior turbinate hypertrophy. Methods: This prospective, cross-sectional study was performed on 52 patients who were referred for Computed tomography of PNS with deviated nasal septum having compensatory hypertrophy of contralateral inferior turbinate. Non-hypertrophied inferior turbinate on the side of deviation was taken as a control group. Deviation angle, mucosal thickness including medial and lateral and bone thickness were evaluated using three-dimensional CT scan and compared to the control group. Result: Dimensions of the bony and mucosal components of the inferior turbinate were significantly greater than those of the control group. This study included 52 patients (M- 30, F- 22) having a mean age of 37 years. Out of 52, the septum deviated to the left side in 56% and 44% to the right side. The average angle of deviation was 10.12°. There was a statistically significant correlation (p<0.05) between total turbinate thickness and angle of deviation. A statistically significant correlation (p<0.05) was also observed between medial mucosa and bone thickness. Conclusion: Compensatory hypertrophy of inferior turbinate in patients with deviated nasal septum not only involves the mucosal component but also the bone itself. Pre-operative CT scan of PNS helps evaluate dimension and composition of inferior turbinate and assists to decide on surgical technique to fix turbinate.